Implementing Personal Construct Theory to explore divergent approaches to substantive knowledge in RE - Flanagan, Ruth (Journal of Religious Education, 2023)
Divergence is not a new phenomenon in RE in England and Wales. A diverse range of aims and approaches have been promoted since RE provision became compulsory in 1944. Approaches include the phenomenological, interpretative, and dialogic with current debates centring around the benefits and challenges of a "worldviews approach". There have been a range of responses to this approach, and implementation has been diverse. It may appear that at the heart of this divergence is confusion over the definition of the term "worldview" and what this entails for teachers: adding content knowledge and diverse sources. However, this paper argues that the divergence is much more significantly rooted in the nature of "substantive knowledge" and the power dynamics associated with who defines, selects and assesses the validity of substantive knowledge. In current research, I am testing the hypothesis that teachers' personal worldviews influence their choice of substantive knowledge in RE. Through 142 questionnaires and 21 interviews, this power dynamic is being investigated. Employing Kelly's (Kelly, Personal construct psychology, Norton, 1955) Personal Construct Theory illuminated teachers' personal worldviews relating to substantive knowledge in RE. Through the completion and analysis of RepGrids, the teachers revealed they taught the "good" aspects of religions and ignored the "bad". They prized knowledge from lived experience above knowledge provided by religious institutions and some deemed online sources more useful than those from religious institutions. The power to define "substantive" knowledge, once primarily in the hands of religious institutions, has dissipated to embrace definitions from teachers' personal worldviews. Whilst enabling a diversity of beliefs to be covered, without examination, hegemonic power may risk the validity of the subject. What is needed, in the midst of this divergence, is not a battle for supremacy, and a rejection of one voice over the other, but an acknowledgement of the power dynamics in defining substantive knowledge in RE.